Tailoring advanced breast cancer treatment after cyclin-dependent kinase 4/6 inhibitors progression - real-world data analysis - Kubeczko, Marcin; Polakiewicz-Gilowska, Anna; Świderska, Katarzyna; Leśniak, Aleksandra; Mianowska-Malec, Marta; Łanoszka, Barbarba; Chomik, Konstanty; Grandys, Barbara; Lisovska, Natalya; Bobek-Billewicz, Barbara; Chmielik, Ewa; Jarząb, Michał (Frontiers in Oncology, 2024)
Background. Cyclin-dependent kinase 4/6 inhibitors (CDK4/6i) represent the gold standard of the hormone receptor positive human epidermal growth factor receptor 2 (HER-2) negative advanced breast cancer. However, optimal treatment after disease progression is a matter of debate. We aimed to assess predictive and prognostic factors associated with the treatment outcome following CDK4/6i progression.Methods. We retrospectively analyzed patients who progressed on CDK4/6i treatment between 2018 and 2024. Treatment based on molecular findings (PIK3CA mutation), genetic findings (BRCA1/2 germline mutation), or adapted to the change in the tumor phenotype in rebiopsy (anti-HER2 therapy in the transformation to HER-2-positive disease) was grouped into tailored treatment and compared to the endocrine-based therapy and chemotherapy alone.Results. Five hundred twelve patients were treated with CDK4/6i. Two hundred patients with disease progression were enrolled in the study. Duration of response to CDK4/6i was not predictive of the response to subsequent treatment, whereas the progression in the central nervous system was the worst prognostic factor. Thirty patients were ineligible for subsequent treatment. Survival after CDK4/6i progression was significantly longer in patients eligible for tailored treatment. The median PFS in patients with tailored treatment (n=19) was 13.5 months vs. 4.9 months in patients with non-tailored therapy (n=151; p=0.045). 12-month PFS was 54.1% with tailored treatment [95% CI 24.1-76.7%] compared to 18.5% with non-tailored therapy [95% CI 11.6-26.6%]. The median OS for patients treated with a tailored approach was not reached compared to 11.5 months with non-tailored treatment (p=0.016). The 24-month OS for patients treated with a tailored approach was 80.2% [95% CI 40.3-94.8%] compared to 21.1% [95% CI 12.2-31.7%] for patients with non-tailored treatment.Tailoring of subsequent treatment strategy seems to be essential for achieving long-term benefit. Further studies are required, as the prognosis after CDK4/6i progression remains dismal, especially in cases affecting the central nervous system.